Ang pagpangayaw sa dutang ginsaad a study of Ilonggo migration and settlement in Tacurong, Cotabato, 1951-1960's. - Arellano, Bernardo Muerong III
The study is significant in identifying issues that were encountered by early migrants which are being confronted today by the citizens of Socsksargen-Cotabato Region or Central Mindanao Region.